Sustainability As: An Analysis of the Alberta Oil Sands Industry’s Metaphorical Discourse - Berry, Megan Nicole (Consilience, 2015)
Analysis of the Alberta oil sands industry’s sustainability perspectives from a communication, and specifically metaphorical, standpoint is a valuable endeavour due to the importance of the oil sands (both in Alberta and elsewhere) today with the world’s reliance on fossil fuels. Learning how sustainability is used and conceptualized by the industry will reward us with a more comprehensive understanding of how to approach industry sustainable development. Moreover, analysing the industry’s sustainability metaphors in a systematic manner will allow a greater variety of metaphors to be introduced and investigated, allowing us to more succinctly articulate metaphorical conceptualizations of sustainability, sustainable and energy development, environmentalism, nature, and the oil sands.